PT Freeport Indonesia – The transition to underground production - Casten, T; Johnson, M; Zimmer, C; Mahayasa, M (MassMin 2020: Eighth International Conference & Exhibition on Mass Mining, 2020)
This paper will discuss the production history, current challenges and the future plans for the PT Freeport Indonesia (PTFI) minerals district as it transitions from primarily open-pit production to a series of large volume caving mines. The Grasberg open pit commenced mining in 1989 and completed at the end of 2019, having mined over 1.37 billion tonnes of ore and having produced 27 billion lbs of payable copper as well as 46 million ozs of payable gold. In addition to the ore mined, the pit also moved over 3.4 billion tonnes of overburden during this timeframe. This paper discusses the rapid mining process, challenges encountered and the pivotal role the Grasberg open pit played in supporting the future underground era. PTFI has been cave mining since the 1980s and has ramped up production over time with a series of progressively deeper mining horizons in the East Ertsberg Skarn System (EESS). Currently, the Deep Ore Zone (DOZ) mine is in active production and is the third lift in the EESS. In 2004, an access development named the AB Adits commenced at a mining horizon approximately 500 m below the DOZ mine. This allowed the fourth lift in the EESS, the Deep MLZ (DMLZ) mine to be constructed. The DMLZ initiated caving in 2015 and is currently ramping up production. In addition, the AB Adits allowed timely access to the downward extension of the Grasberg ore body, and the Grasberg Block Cave mine initiated caving in 2018 and is also undergoing a rapid production ramp-up. These long-lived, high-volume caving operations will extend the life of the mineral district past 2040 with a plan to produce approximately 200 - 250 ktpd at peak production rates. The paper will discuss the strategic plans applied to construct these large and long-lead projects and some of the challenges faced during the 16 years of pre-production, cave initiation and production ramp up. Critical topics such as rapid access, infrastructure construction, ground control, wet muck mitigation and seismicity are discussed in the paper, focusing on lessons learned and ongoing improvements.